Chemical Sensors and Electronic Noses Based on 1-D Metal Oxide Nanostructures - Chen, Po-Chiang; Shen, Guozhen; Zhou, Chongwu (IEEE transactions on nanotechnology, 2008)
The detection of chemicals such as industrial gases and chemical warfare agents is important to human health and safety. Thus, the development of chemical sensors with high sensitivity, high selectivity, and rapid detection is essential and could impact human beings in significant ways. 1-D metal oxide nanostructures with unique geometric and physical properties have been demonstrated to be important candidates as building blocks for chemical sensing applications. Chemical sensors composed of a wide range of pristine 1-D metal oxide nanostructures, such as In 2 O 3 , SnO 2 , ZnO, TiO 2 , and CuO, have been fabricated, and exhibited very good sensitivity in the detection of important industrial gases, chemical warfare agents, and human breath. In this review, we provide an overview of this chemical sensing field. Various key elements of the topics will be reviewed, including 1-D metal oxide nanostructure synthesis, electronic properties of nanowire-based FETs, and their chemical sensing behaviors. In addition, this paper provides a review of the recent development of electronic nose systems based on metal oxide nanowires, which indicate great potential for the improvement of sensing selectivity.